Zinc Chloride-Doped g-C3N4 Microtubes for Enhanced Photocatalytic Degradation of Tetracycline Hydrochloride - Ye, Xiao-Yu (Langmuir : the ACS journal of surfaces and colloids, 2025)
Morphology regulation and element doping are effective means to improving the photocatalytic performance of graphite-phase carbon nitride (g-C3N4). In this article, using melamine and zinc chloride as raw materials, a novel kind of Zn/Cl-doped hollow microtubular g-C3N4 (Zn-HT-CN) by a hydrothermal method was developed. The structure and morphology of Zn-HT-CN and reference samples were characterized by X-ray diffraction patterns (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), etc. The doping of Zn/Cl narrowed the bandgap width of the hollow microtubular g-C3N4, as well as the inhibiting recombination of photogenerated electron and holes. Compared with the pure g-C3N4 microtube, Zn-HT-CN showed excellent catalytic performance for the photodegradation of tetracycline hydrochloride (TCH) under irradiation of visible light. The photodegradation rate of TCH reached 94.41% in 40 min, which was about two times as high as that catalyzed by the pure g-C3N4 microtube. Moreover, it was also superior to the g-C3N4 microtube doped with other typical metal elements. In addition, Zn-HT-CN showed good tolerance to environmental pH, and the catalytic efficiency of the material remained at 78.78% after five cycles